Analysis of Intermodal Terminals Service Quality in the Republic of Croatia - Abramović, Borna; Lovrić, Ivica; Stupalo, Vlatka (Promet - Traffic&Transportation)
The most common problem that the terminals face is inadequate infrastructure, long waiting times, delays, malfunctions, and unexpected problems due to which terminals are often congested for a long time, high costs, lack of expansion, etc. All this leads to reduced quality of services and the price increase for the user service. These problems do not occur only at the terminal of one type, but at all terminals. At present, the delays and uneconomical operations are unacceptable. Intermodal terminals are not immune to any of the above. In order to increase the service quality and to reduce the cost of transportation and transmission, all the bottlenecks in the process are detected and analyzed in the work. The identification and removal of the bottlenecks in the processes of transport and transfer from the initial to the final terminal increases the quality of services provided to customers. The quality of services includes shorter time of transport and transfer by using shorter routes as well as the acceptable price of the service itself.